Dampak Sosial dan Lingkungan Penambangan Emas Terhadap Kehidupan Masyarakat Gampong Karak Kecamatan Woyla Barat Kabupaten Aceh Barat - Humaira Humaira; Aja Fitria; Mustakhimah Mustakhimah; Ayu Wannira; Juliana Juliana; Muna Lisa; Wulan Sari; Sopar Sinambela (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the social and environmental impacts of gold mining activities on the lives of the people in Gampong Karak, Woyla Barat District, West Aceh Regency. The research employed a descriptive qualitative method with data collection techniques consisting of field observations, in-depth interviews, and documentation. The informants included village officials, community leaders, gold miners, and local residents directly affected by mining activities. The results of the study show that gold mining activities have both positive and negative impacts on the community. From an economic perspective, gold mining has increased community income and created new job opportunities. However, these economic benefits are not sustainable because people’s income highly depends on uncertain mining yields. From an environmental perspective, mining activities have caused river water pollution due to the use of mercury, land degradation, river sedimentation, and increased risks of flooding and landslides. In addition, the quality of the Woyla River water has significantly declined, disrupting the daily activities of residents who depend on the river for household needs and agricultural irrigation. From a social perspective, there has been a shift in livelihoods from agriculture to mining activities, the emergence of social conflicts, and changes in the social life patterns of the village community. This study concludes that the long-term negative impacts of gold mining are more dominant than its economic benefits. Therefore, stronger government supervision, better mining management, and increased public awareness are needed to maintain a balance between economic needs and environmental sustainability.